Navigating turbulence: Hydrogen's role in the decarbonization of the aviation sector - Abdurahman Alsulaiman (The Oxford Institute for Energy Studies, 2024)
This paper offers a comprehensive analysis of the historical evolution and the current state of the aviation industry, with a particular emphasis on the critical need for this sector to decarbonize. It delves into emerging propulsion technologies such as battery electric and hydrogen-based systems, assessing their potential impact on sustainability within the aviation sector. Special attention is devoted to the global regulatory framework, notably carbon offsetting and emission reduction scheme for international aviation, which encapsulates initiatives such as lower carbon aviation fuels and sustainable aviation fuels. Examining the environmental challenges facing aviation, the paper underscores the necessity for a balanced and comprehensive strategy that integrates various approaches to achieve sustainable solutions. By addressing both the historical context and contemporary advances, the paper aims to provide a nuanced understanding of the complexities surrounding aviation's decarbonization journey, acknowledging the industry's strides while recognizing the ongoing challenges in the pursuit of sustainability.
Keywords: 330; Aviation; carbon neutrality; CORSIA; decarbonized flight; Hydrogen; Sustainable Aviation Fuel (SAF)